On the use of a visual census in surveying fish communities in lentic water bodies. (October 2019) - Holubová, Michaela; Čech, Martin; Vašek, Mojmír; Peterka, Jiří
Highlights: Fish abundance did not differ between UVC and hydroacoustic survey methods. Fish species composition did not differ between UVC and purse seining. Properly timed monitoring via UVC produces accurate results. UVC is a method with minimal impact on the ecosystem and the investigated organisms. Abstract: Fishing survey gear often causes damage to the ecosystem and can be size or species selective. Use of an underwater video camera (UVC) omits these flaws, and can bring accurate information on species composition and density of daytime assemblages, moreover it can discover unknown details about behavioural patterns. This study presents a model situation and proposes the use of the UVC as a valid sampling method even in the systems with higher trophies. No significant difference in species composition was found between traditionally used survey gear – purse seining and camera; nor was there a difference in the standardised fish abundance between hydroacoustics and camera when surveying an open water habitat of a temperate freshwater reservoir.